STRATEGI PROMOSI DALAM MENINGKATKAN DAYA TARIK INVESTASI DI PROVINSI SUMATERA UTARA - Nirwaty Tarigan (Akademi Pariwisata Darma Agung, 2019)
Investment and Promotion Agency of North Sumatra Province is the spearhead in attracting both FDI and domestic investment. The agency prepared a material role in the formulation of technical policy in the field of investment and promotion. In order to encourage investment regions, required appropriate promotional strategies to be considered by the local government, thus increasing investment in North Sumatra. Various activities are carried out and followed by the Investment and Promotion Agency of North Sumatra has not a significant impact in increasing investment, increasing promotional activity is not in line with the increase in the value of investments. The purpose of this research is to develop an effective promotional strategy that can increase the expected value of the investment. The population in this study were 7 people who become the most competent and feel the impact of investment promotion in North Sumatra. This type of research in this study is qualitative research, the data analysis through SWOT analysis. The results of data analysis showed that the stability strategy is an appropriate strategy to improve the effectiveness of investment promotion in North Sumatra. Stability Strategy aims to be diversified range of media campaigns and promotional activities increased intensity.